Exploring chronic disease in Bolivia: A cross-sectional study in La Paz - Abbott, Patricia (PLoS One, 2018)
PURPOSE: This study seeks to develop an understanding that can guide development of programs to improve health and care for individuals with Non-Communicable Diseases (NCDs) in La Paz, Bolivia, where NCDs are prevalent and primary care systems are weak. This exploratory investigation examines the characteristics of chronic disease patients in the region, key health related behaviors, and their perceptions of the care that they receive. The longer-term goal is to lay groundwork for interventional studies based on the principles of the Chronic Care Model (CCM). SUBJECTS AND METHODS: The study is based on two surveys of adults (> 18 years old) administered in 2014 in La Paz, Bolivia. A total of 1165 adult patients participated in the first screening survey. A post-screening second survey, administered only on those who qualified based on Survey 1, collected more detailed information about the subjects’ general health and health related personal circumstances, several health behaviors, health literacy, and their perceptions of care received. A final data set of 651 merged records were used for analysis. RESULTS: Characteristic of a low-income country, the majority of participants had low levels of education, income, health literacy and high rates of under/unemployment. Nearly 50% of participants reported 2 or more NCDs. Seventy-four percent (74%) of respondents reported low levels of medication adherence and 26% of the population was found to have an undiagnosed depressive disorder. Overall, the perception of care quality was low (60%), particularly in those under the age of 45. Significant relationships emerged between several sociodemographic characteristics, health behaviors, and perceptions that have major implications for improving NCD care in this population. CONCLUSIONS: These findings illustrate some of the challenges facing low-income countries where reversing the tide of NCDs is of great importance. The prevalence of NCDs coupled with challenging social determinants of health, poor medication adherence, low health literacy, and perceptions of low quality of healthcare highlight several areas of opportunity for intervention.